Phytopathological screening and molecular marker analysis of wheat germplasm from Kazakhstan and CIMMYT for resistance to tan spot - A. M. Kokhmetova; M. N. Atishova; M. T. Kumarbayeva; I. N. Leonova (Вавиловский журнал генетики и селекции)
Tan spot caused by the fungus Pyrenophora tritici-repentis is an important leaf spot disease in wheat growing areas throughout the world. The study aims to identify wheat germplasm resistant to tan spot based on phytopathological screening and molecular marker analysis. A collection of 64 common wheat germplasms, including cultivars and breeding lines from Kazakhstan and CIMMYT, was assessed for tan spot resistance in greenhouse conditions and characterized using the Xfcp623 molecular marker, diagnostic for the Tsn1 gene. All wheat cultivars/lines varied in their reaction to tan spot isolate race 1, ranging from susceptible to resistant. Most accessions studied (53 %) were susceptible to Ptr race 1. Spring wheat cultivars were more susceptible to race 1 than winter wheat cultivars. As a result of genotyping, an insensitive reaction to Ptr ToxA was predicted in 41 wheat cultivars (64 %). The tsn1 gene carriers identified included 27 Kazakhstani and 14 CIMMYT cultivars/lines, demonstrating insensitivity to Ptr ToxA. The majority of the Tsn1 genotype were sensitive to race 1 and showed susceptibility to the pathogen in the field. Disease scores from seedling stage positively correlated with field disease ratings. Of particular interest are 27 wheat accessions that demonstrated resistance to spore inoculation by Ptr race 1, were characterized by insensitivity to ToxA and showed field resistance to the pathogen. The results of this study will contribute to wheat breeding programs for tan spot resistance with Marker Assisted Selection using the closely flanking markers.